التفتيش في الجريمة المعلوماتية - بن طالب, ليندا (جامعة الوادي University of Eloued, 2017)
إن التفتيش في الجريمة المعلوماتية إجراء صعب بالنظر إلى طبيعة الدليل المتحصل منه والذي يسهل إخفاءه وتدميره، وقد يتصل بدول أخرى مما يزيد صعوبة في الحصول عليه نظرا لتمسك كل دولة بسيادتها. كما أن التفتيش في الأنظمة الإلكترونية يحتاج إلى معرفة علمية وفنية قد لا تتوفر لدى رجال الشرطة والمحققين والقضاة. كما يجوز أن يصدر إذن التفتيش مقتصرا على تفتيش الكمبيوتر، فإذا كان هذا الأخير متواجدا في أحد المساكن، يتعين توفر شروط تفتيش المساكن، أما إذا كان الكمبيوتر في حيازة شخص خارج مسكنه أو كان في سيارته خارج المسكن، فإنه يكفي توفر شروط تفتيش الشخص. عند صدور إذن بتفتيش نظام معين لمعالجة المعلومات آليا للحصول على دليل يفيد في كشف الحقيقة عن جريمة معلوماتية معينة، يجوز تفتيش كل الملفات المتواجدة في النظام. إذا أسفر التفتيش عن ضبط البيانات المتواجدة في نظام المعالجة الآلية، فيمكن ضبطها دون ضبط النظام كله، وذلك بأخذ نسخة من البيانات الموجودة، ويلتزم المحقق بالتحفظ عليها بشكل يمنع العبث بها. Abstract: Inspection of cybercrime is difficult because of the nature of the obtained evidence, which is easy to hide and to destroy, it may also be related to other countries, making it more difficult to obtain because each country has its own sovereignty. Inspection of electronic systems also requires scientific and technical knowledge that may not be available to police officers, investigators and judges. An inspection permit may be issued only for computer inspection. If the latter is present in a dwelling, the conditions for house inspection must be met, whether the computer is in the possession of a person outside his home or in his car outside the dwelling. When an order is issued for the inspection of a particular system to process the information automatically in order to obtain evidence to reveal the truth about a particular information crime, all files in the system may be searched. If the inspection results in the control of the data contained in the automated processing system, it can be set without controlling the whole system, by taking a copy of the existing data, and the investigator is obliged to reserve on it in a way that prevents tampering.
Keywords: التفتيش؛ البيئة الإلكترونية؛ الإذن بالتفتيش؛ الحاسوب؛ السلطة المختصة؛ الجرائم المعلوماتية